Functional Roles of Complexin in Neurotransmitter Release at Ribbon Synapses of Mouse Retinal Bipolar Neurons - Vaithianathan, Thirumalini (J Neurosci, 2015)
Ribbon synapses of photoreceptor cells and bipolar neurons in the retina signal graded changes in light intensity via sustained release of neurotransmitter. One molecular specialization of retinal ribbon synapses is the expression of complexin protein subtypes Cplx3 and Cplx4, whereas conventional synapses express Cplx1 and Cplx2. Because complexins bind to the molecular machinery for synaptic vesicle fusion (the SNARE complex) and modulate transmitter release at conventional synapses, we examined the roles of ribbon-specific complexin in regulating release at ribbon synapses of ON bipolar neurons from mouse retina. To interfere acutely with the interaction of native complexins with the SNARE complex, a peptide consisting of the highly conserved SNARE-binding domain of Cplx3 was introduced via a whole-cell patch pipette placed directly on the synaptic terminal, and vesicle fusion was monitored using capacitance measurements and FM-dye destaining. The inhibitory peptide, but not control peptides, increased spontaneous synaptic vesicle fusion, partially depleted reserve synaptic vesicles, and reduced fusion triggered by opening voltage-gated calcium channels under voltage clamp, without affecting the number of synaptic vesicles associated with ribbons, as revealed by electron microscopy of recorded terminals. The results are consistent with a dual role for ribbon-specific complexin, acting as a brake on the SNARE complex to prevent spontaneous fusion in the absence of calcium influx, while at the same time facilitating release evoked by depolarization.